2015
DOI: 10.1590/s0100-736x2015000300014
|View full text |Cite
|
Sign up to set email alerts
|

Análise quantitativa da ecogenicidade testicular pela técnica do histograma de ovinos da baixada ocidental maranhense

Abstract: RESUMO.-A ultrassonografia é um método de diagnóstico por imagem que permite a avaliação de diferentes órgãos e estruturas corpóreas de maneira não invasiva. No entanto, a avaliação subjetiva das imagens caracteriza um dos grandes entraves na utilização desta técnica de diagnósti-co, havendo necessidade de mecanismos que minimizem a subjetividade do exame e a divergência na interpretação dos achados ultrassonográficos. Desta forma este trabalho objetivou caracterizar a ecogenicidade do parênquima e mediastino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(53 reference statements)
0
4
2
6
Order By: Relevance
“…These results were similar to those found by Gouletsou et al (2003), Amorim (2010), Andrade et al (2012), and Andrade et al (2014). Silva et al (2015) observed values lower than those found in pre-pubertal and pubertal groups, which were near 70.20 pixels (3 to 6 months old) and 91.44 pixels (7 to 12 months old) for crossbred sheep. However, these authors found an average near 112.84 pixels in 13 to 18 month-old sheep, which was higher than that found in the sexually mature group.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…These results were similar to those found by Gouletsou et al (2003), Amorim (2010), Andrade et al (2012), and Andrade et al (2014). Silva et al (2015) observed values lower than those found in pre-pubertal and pubertal groups, which were near 70.20 pixels (3 to 6 months old) and 91.44 pixels (7 to 12 months old) for crossbred sheep. However, these authors found an average near 112.84 pixels in 13 to 18 month-old sheep, which was higher than that found in the sexually mature group.…”
Section: Discussioncontrasting
confidence: 59%
“…The average value of testicular volume of pre-pubertal group was lower than that found by Pacheco (2008) (2000) and Silva et al (2015), according to which, the testicular parenchyma has a homogeneous echo texture; then, if both antimeres do not have the same echogenicity, disease should be suspected.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Visual inspection of ultrasound (US) examination is insufficient to accurately determine the echogenicity and echotexture of the evaluated tissues. Consequently, techniques that enable quantification of the region of interest (ROI) have been created, thus allowing minimization of image interpretation errors (Maeda et al 1998, Silva et al 2015, Dantas et al 2016, Mendonça 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound findings are subjective and produce many discrepancies either due to the ultrasound system variability or to the operator's experience. The GSH can help in diagnostics interpretation and has become an increasingly used tool both in clinical routine and in research (Osawa & Mori 1996, Ferreira & Rasband 2012, Silva et al 2015, Fogaça 2018, Castiglioni et al 2018.…”
Section: Introductionmentioning
confidence: 99%